Understanding global slavery : a reader - Bales, Kevin (University of California Press, 2005)
Slavery continues as a blight on the human world, with an estimated 27 million people around the world in bondage. Kevin Bales undertakes a discussion of the causes of enslavement & the socio-economic factors that sustain slavery in the 21st century.
Keywords: Slavery.; Slave labor.; Forced labor.; Prostitution.; Slave trade.; Sex Work; Esclavage.; Esclaves -- Travail.; Travail forcé.; Traite des esclaves.; slavery.; prostitution.; SOCIAL SCIENCE -- Slavery.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Forced labor; Prostitution; Slave labor; Slave trade; Slavery; Frauenhandel; Menschenhandel; Sklavenhandel; Sklaverei; abolition.; academic.; antislavery.; crime.; criminal justice.; current affairs.; economics.; economy.; ethics.; expose.; global economy.; global issues.; global slavery.; globalization.; human rights.; human trafficking.; international.; modern slavery.; morals.; pakistan.; phenomenon.; politics.; race issues.; race.; racism.; redemption.; scholarly.; servitude.; thailand.; true story.; us history.; Electronic books.